2021
DOI: 10.3390/horticulturae8010002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Entomopathogenic Trichoderma Isolates against Sugarcane Woolly Aphid, Ceratovacuna lanigera Zehntner (Hemiptera: Aphididae)

Abstract: Ceratovacuna lanigera Zehntner (Hemiptera: Aphididae) is a destructive insect pest of sugarcane that is responsible for reducing the quality, yield, and sugar content. Ecofriendly methods of pest control, such as the use of biological control, is encouraged since it does not exhibit the harmful effects that are usually seen when using chemical-based pesticides. Here, we evaluated the efficacy of several entomopathogenic fungi isolates against C. lanigera under laboratory conditions. A total of seven isolates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…In the present study, the obtained results enabled the identification and separation of isolates in three different taxonomic groups: T. asperellum (BRS-1, BRS-3 and BRS-4), T. harzianum (BRS-2, BRS-5, BRS-6, BRS-7 and BRS-8), and T. koningiopsis (BRS-9). These findings are closed to those obtained by others authors, including Islam et al (2021),who identified 7 isolates of Trichoderma spp. obtained from agricultural soils collected from Sabah, Malaysia, using a combination of morphological and molecular data from the ITS 1-5.8S-ITS 2 regions of the rDNA.…”
Section: Discussionsupporting
confidence: 51%
“…In the present study, the obtained results enabled the identification and separation of isolates in three different taxonomic groups: T. asperellum (BRS-1, BRS-3 and BRS-4), T. harzianum (BRS-2, BRS-5, BRS-6, BRS-7 and BRS-8), and T. koningiopsis (BRS-9). These findings are closed to those obtained by others authors, including Islam et al (2021),who identified 7 isolates of Trichoderma spp. obtained from agricultural soils collected from Sabah, Malaysia, using a combination of morphological and molecular data from the ITS 1-5.8S-ITS 2 regions of the rDNA.…”
Section: Discussionsupporting
confidence: 51%
“…Further examination indicated that there was an intense parasitic growth of the T. gamsii hyphae across the lower abdomen and respiratory ostiole of the Delia radicum larva [175]. Other than that, T. harzianum, T. asperellum, and T. hamatum showed pathogenic potential against Cetarovacuna lanigera, a destructive insect pest of sugarcane that is responsible for reducing the quality, yield, and sugar content [176].…”
Section: Trichoderma As a Biocontrol Agent Against Other Plant Pathog...mentioning
confidence: 99%
“…Laboratory studies showed that Trichoderma spp. negatively influence both piercing-sucking [ 26 , 33 , 34 , 35 , 72 ] and chewing insects [ 27 , 33 ]. In addition, Trichoderma spp.…”
Section: Discussionmentioning
confidence: 99%